2016
DOI: 10.1111/exd.12966
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐released growth factors induce the antimicrobial peptide human beta‐defensin‐2 in primary keratinocytes

Abstract: Platelet-released growth factors (PRGF) and its related clinically used formulations [e.g. Vivostat platelet-rich fibrin (PRF(®) )] are thrombocyte concentrate lysates that support healing of chronic, hard-to-heal and infected wounds. Human beta-defensin-2 (hBD-2) is an antimicrobial peptide expressed in human keratinocytes exhibiting potent antimicrobial activity against wound-related bacteria. In this study, we analysed the influence of PRGF on hBD-2 expression in human primary keratinocytes and the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 79 publications
3
55
0
2
Order By: Relevance
“…hBD‐1 is constitutively expressed in the skin, respiratory and urogenital tissues; however, it is also inducible in the epidermis following challenge with lipopolysaccharide (LPS) and peptidoglycan . The expression of hBD‐2 to hBD‐4 is generally inducible following stimulation with microorganisms, inflammation, wound healing and injury . In the human skin, hBD‐1 to hBD‐3 are detected in the differentiated layers of the epidermis.…”
Section: Major Families Of Human Skin‐derived Amps/hdpsmentioning
confidence: 99%
See 1 more Smart Citation
“…hBD‐1 is constitutively expressed in the skin, respiratory and urogenital tissues; however, it is also inducible in the epidermis following challenge with lipopolysaccharide (LPS) and peptidoglycan . The expression of hBD‐2 to hBD‐4 is generally inducible following stimulation with microorganisms, inflammation, wound healing and injury . In the human skin, hBD‐1 to hBD‐3 are detected in the differentiated layers of the epidermis.…”
Section: Major Families Of Human Skin‐derived Amps/hdpsmentioning
confidence: 99%
“…These observations suggest that AMPs/HDPs are promising therapeutic agents for skin wound healing. Upregulation of AMPs/HDPs at the wound surface is mediated in part by cytokines and growth factors . While the expression of LL‐37 was also observed during the inflammatory stage of the wound‐healing process, peak production of skin‐derived AMPs/HDPs, including hBD‐2, hBD‐3, S100A proteins, elafin, lactoferrin and secretory leucocyte protease inhibitor (SLPI), was observed during the proliferative phase .…”
Section: Role Of Amps/hdps In Human Skin Diseasesmentioning
confidence: 99%
“…Even though these cytokines are cell proliferation mediators, they also constitute the main axis of planned cell death (apoptosis), [14] inducing survival signals that are able to protect cells from many apoptotic stimuli. Bayer, et al (2016) [15] explored for the first time the PRF properties, which might contribute to its anti-anti-inflammatory/antimicrobial activities. It was found that in human keratinocytes, PRF was able to induce hBD-2 (�-defensin 2).…”
Section: Prf Various Types' Effects On Growth Factors Releasementioning
confidence: 99%
“…[5,6] Although PRF does show an antibacterial effect, there are no data, that PRF-monotherapy has benefits in the treatment of infected wounds, but infections seem to impair the healing process. [7–10] Therefore, although compelling data is lacking, in treatment or prophylaxis of infected wounds PRF is often combined with antiseptics, such as polyhexanide, or antibiotics, such as vancomycin, teicoplanin, gentamicin or amikacin with the intent to eradicate bacteria and increase the healing process. In the clinical setting it is common that dressings of infected wounds, treated with PRF, are changed once a week only.…”
Section: Introductionmentioning
confidence: 99%